A evolução demográfica da freguesia do Bonfim da cidade do Porto na época contemporânea - Correia, Luís Grosso (História: revista da Faculdade de Letras da Universidade do Porto, 2018)
This article was requested by the parish of Bonfim, in the city of Porto, in the 1990’s. It was delivered in 1999, but was not published. The aim of the present work is to define the specific identity of the socio-demographic development of the Bonfim parish in the context of the city of Porto during the 19th and 20th centuries. The results presented are based on the data available at that time, both from local and religious authorities, as well as from official statistics.